PENGARUH KUALITAS PELAYANAN ADMINISTRASI AKADEMIK DAN KEMAHASISWAAN TERHADAP KEPUASAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN BENGKULU - Sumarni, Yenti (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
This study aimed to analyze the quality of academic administration and students services in IAIN Bengkulu. The sampling technique was done by using purposive sampling, where in this case, the selected respondents are students who use the services of Academic Administration and Student Affairs who are active students from the beginning until the end of the semester with a sample size obtained that consists of 100 respondents. The data analysis was performed by using multiple linear regression analysis results from several related quality of academic administrative services obtained that the better the quality of Academic and Student Administration services, the higher satisfaction of students of the Faculty of Islamic Economy will be.